Influence of tumor cell-derived TGF-β on macrophage phenotype and macrophage-mediated tumor cell invasion - Maldonado, Laura Andrea González [UNESP] (2022)
In oral squamous cell carcinoma (OSCC), macrophages are the most abundant immune cell type in the tumor microenvironment (TME). Macrophage infiltration is inversely proportional to prognosis and disease survival, particularly when these tumor-associated macrophages (TAM) assume an M2-like phenotype. This phenotype is determined by cues from the microenvironment, especially tumor cell-secreted molecules, and is associated with increased production of extracellular-matrix-degrading enzymes, angiogenic molecules and immunosuppressing cytokines. This study investigates, in vitro and in vivo, the relative contribution of OSCC cell-secreted transforming growth factor beta (TGF-β) on the phenotype of macrophages and on macrophage-facilitated tumor invasion. TCGA database shows a positive correlation between high expression of TGFB1 and macrophage infiltrate in Head and neck squamous cell carcinoma (HNSCC). THP-1 derived-macrophages were exposed to the secretome of two OSCC cell lines using two strategies to block the effects of neoplastic cell-secreted TGF-β: pre-treatment with a TGF-β receptor type I kinase inhibitor (LY364947) and antibody-mediated depletion. RT-qPCR, ELISA and flow cytometry determined macrophage phenotype after exposure to conditioned medium (CM) from H-314 (TGF-βhigh) or SCC-9 (TGF-βlow) cell lines. The influence of TGF-β on macrophage-mediated tumor cell invasion (myogel and CAM assays) and chemotaxis (Boyden chamber) was assessed using co-cultures of macrophages and OSCC cells in which macrophages were pre-conditioned with the secretome of OSCC cells in the presence and absence of LY364947. Blocking the effects of TGF-β skewed macrophages to the M1 end of the phenotype by differential effects depending on the strategy for inhibiting the influence of TGF-β and on the neoplastic cell secretome. In vitro and in vivo invasion of H-314 cell line was reduced by inhibiting TGFBR1 signaling in macrophages, whereas SCC-9 cell invasion was not affected. SCC-9/macrophage reciprocal chemotaxis were enhanced by inhibiting TGFBR1 signaling in macrophages, whereas only macrophage chemotaxis to H314 products was inhibited by inhibiting TGFBR1. In summary, blocking the effects of OSCC cell-secreted TGF-β in macrophages attenuates M2-like phenotypical traits of macrophages and can impact invasion and chemotaxis of tumor cells differentially.